ANALISIS KONTRASTIF AFIKSASI VERBA BAHASA JAWA DENGAN BAHASA INDONESIA - Agus Bambang Hermanto (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study sought to describe the similarities and differences between Javanese and Indonesian so that the Indonesian learning, teachers can anticipate the inference to be performed by learners. Java language, a research study with a cognate language Malay so that this language has much in common with the elements contained in Indonesian. The problem addressed in this study, namely the form of the verb affixes system contrastive Javanese and Indonesian. The method used in this research is descriptive qualitative content analysis techniques. The theory used is the theory of contrastive analysis. The findings obtained from the results of this study, there are similarities and differences in the form of the verb affixes system contrastive Javanese and Indonesian.